Facing the Future: Effects of Short-Term Climate Extremes on Isoprene-Emitting and Nonemitting Poplar. Issue 1 (10th July 2015) - Vanzo, Elisa; Jud, Werner; Li, Ziru; Albert, Andreas; Domagalska, Malgorzata A.; Ghirardo, Andrea; Niederbacher, Bishu; Frenzel, Juliane; Beemster, Gerrit T.S.; Asard, Han; Rennenberg, Heinz; Sharkey, Thomas D.; et al.
Abstract : The ability to emit isoprene does not protect poplar trees from realistic short-term and periodic drought and heat waves under proposed future conditions. Abstract: Isoprene emissions from poplar ( Populus spp.) plantations can influence atmospheric chemistry and regional climate. These emissions respond strongly to temperature, [CO2 ], and drought, but the superimposed effect of these three climate change factors are, for the most part, unknown. Performing predicted climate change scenario simulations (periodic and chronic heat and drought spells [HDS s] applied under elevated [CO2 ]), we analyzed volatile organic compound emissions, photosynthetic performance, leaf growth, and overall carbon (C ) gain of poplar genotypes emitting (IE ) and nonemitting (NE ) isoprene. We aimed (1) to evaluate the proposed beneficial effect of isoprene emission on plant stress mitigation and recovery capacity and (2) to estimate the cumulative net C gain under the projected future climate. During HDS s, the chloroplastidic electron transport rate of NE plants became impaired, while IE plants maintained high values similar to unstressed controls. During recovery from HDS episodes, IE plants reached higher daily net CO2 assimilation rates compared with NE genotypes. Irrespective of the genotype, plants undergoing chronic HDS s showed the lowest cumulative C gain. Under control conditions simulating ambient [CO2 ], the C gain was lower in the IE plants than in the NE plants. In summary, the data on the overall C gain and plant growth suggest that the beneficial function of isoprene emission in poplar might be of minor importance to mitigate predicted short-term climate extremes under elevated [CO2 ]. Moreover, we demonstrate that an analysis of the canopy-scale dynamics of isoprene emission and photosynthetic performance under multiple stresses is essential to understand the overall performance under proposed future conditions.